JUDICIAL INVOLVEMENT IN DOMAIN NAME DISPUTES IN CANADA - Campbell, R. (Revue de droit de l'Université de Sherbrooke, 2003)
Early domain name challenges were primarily resolved by application to the courts for an injunction. To obtain this relief, challengers argued that the use of the domain name infringed a private law right. Today, most current domain name disputes are resolved by recourse to a dispute resolution policy set up by contract at the time a domain name is registered. The rights of both parties are carefully balanced in the relevant policy and a written decision is required of the panel.What is the status of such a decision after completion of the alternate dispute resolution process vis-à-vis subsequent court intervention? Does a court have jurisdiction to hear the dispute de novo by way of an application for declaration? Application of traditional administrative law principles of collateral attack and issue estoppel do not support de novo judicial intervention. Nor do the administrative law principles for judicial review of consensual tribunal decisions clearly support court intervention.